A Drosophila neurexin is required for septate junction and blood-nerve barrier formation and function. - Baumgartner, S.; Littleton, J.T.; Broadie, K.; Bhat, M.A.; Harbecke, R.; Lengyel, J.A.; Chiquet-Ehrismann, R.; Prokop, A.; Bellen, H.J. (Cell, 1996)
Septate and tight junctions are thought to seal neighboring cells together and to function as barriers between epithelial cells. We have characterized a novel member of the neurexin family, Neurexin IV (NRX), which is localized to septate junctions (SJs) of epithelial and glial cells. NRX is a transmembrane protein with a cytoplasmic domain homologous to glycophorin C, a protein required for anchoring protein 4.1 in the red blood cell. Absence of NRX results in mislocalization of Coracle, a Drosophila protein 4.1 homolog, at SJs and causes dorsal closure defects similar to those observed in coracle mutants. nrx mutant embryos are paralyzed, and electrophysiological studies indicate that the lack of NRX in glial-glial SJs causes a breakdown of the blood-brain barrier. Electron microscopy demonstrates that nrx mutants lack the ladder-like intercellular septa characteristic of pleated SJs (pSJs). These studies identify NRX as the first transmembrane protein of SJ and demonstrate a requirement for NRX in the formation of septate-junction septa and intercellular barriers.